Analysis of Passenger Rates on Traditional Ships on the Tarabunga- Tamba Route, Samosir Regency, North Sumatra Province - Tungkup, Doharman Lumban; Santoso, Santoso; Febriansyah, Febriansyah; Jaya Perkasa, Muhammad Elga; Amrillah, Muhamad Fahmi (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2023)
Tarabunga Pier is a pier located in Palipi District, Samosir Regency, North Sumatra Province which serves the Tarabunga – Tamba route. In organizing crossings, tariffs greatly influence the level of transportation services, especially in fulfilling community services. However, the tariff for the Tarabunga-Tamba route currently in effect is not in accordance with Minister of Transportation Regulation Number PM. 61 of 2021. This research aims to determine the ship operational costs (BOK) for the Tarabunga-Tamba route based on Minister of Transportation Regulation Number PM. 61 of 2021. The research methodology used is direct observation in the field, interviews, documentation and literature/institutional studies. Then, to analyze it, we are guided by Ministerial Regulation Number 61 of 2021 concerning Management of River and Lake Transportation. The analysis used is load factor analysis, ship operational cost analysis and unit rate analysis. The results of this research are that the rates set are not in accordance with the results obtained by researchers based on the calculation of ship operational costs (BOK), namely IDR 1,000/passenger and IDR 3,000 /motorcycle. The tariff for the Tarabunga – Tamba route currently refers to Regent Regulation Number 49 of 2017 (Horsik – Ajibata). This is not relevant because the track distance is different. Meanwhile, based on the Ability to Pay calculation of Rp. 2,733 and Willingness to Pay Rp. 1,008.